Glycosaminoglycan Chain of Dentin Sialoprotein Proteoglycan - Zhu, Q. (SAGE Publications, 2010)
Dentin sialophosphoprotein (DSPP) is processed into dentin sialoprotein (DSP) and dentin phosphoprotein. A molecular variant of rat DSP, referred to as “HMW-DSP”, has been speculated to be a proteoglycan form of DSP. To determine if HMW-DSP is the proteoglycan form of DSP and to identify the glycosaminoglycan side-chain attachment site(s), we further characterized HMW-DSP. Chondroitinase ABC treatment reduced the migration rate for portions of rat HMW-DSP to the level of DSP. Disaccharide analysis showed that rat HMW-DSP contains glycosaminoglycan chains made of chondroitin-4-sulfate and has an average of 31-32 disaccharides/mol. These observations confirmed that HMW-DSP is the proteoglycan form of DSP (renamed “DSP-PG”). Edman degradation and mass spectrometric analyses of tryptic peptides from rat DSP-PG, along with substitution analyses of candidate Ser residues in mouse DSPP, confirmed that 2 glycosaminoglycan chains are attached to Ser(241) and Ser(253) in the rat, or Ser(242) and Ser(254) in the mouse DSPP sequence.